2021
DOI: 10.1007/jhep03(2021)020
|View full text |Cite
|
Sign up to set email alerts
|

Slow scrambling in extremal BTZ and microstate geometries

Abstract: Out-of-time-order correlators (OTOCs) that capture maximally chaotic properties of a black hole are determined by scattering processes near the horizon. This prompts the question to what extent OTOCs display chaotic behaviour in horizonless microstate geometries. This question is complicated by the fact that Lyapunov growth of OTOCs requires nonzero temperature, whereas constructions of microstate geometries have been mostly restricted to extremal black holes.In this paper, we compute OTOCs for a class of extr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 39 publications
2
30
0
Order By: Relevance
“…Agreement was indeed found between this effective description and more conventional CFT methods [1]. Although this is not the primary focus of the present paper, the strong connection between maximal chaos and the AdS/CFT correspondence is worth mentioning as it appears that holographic CFTs are maximally chaotic [15][16][17][18][19][20][21][22].…”
Section: Introductionsupporting
confidence: 62%
“…Agreement was indeed found between this effective description and more conventional CFT methods [1]. Although this is not the primary focus of the present paper, the strong connection between maximal chaos and the AdS/CFT correspondence is worth mentioning as it appears that holographic CFTs are maximally chaotic [15][16][17][18][19][20][21][22].…”
Section: Introductionsupporting
confidence: 62%
“…In this way we reproduce the gravitational results found in [1]. We also study the extremal and zero-temperature limits, which require backing off from some of the approximations used in the previous result, and reproduce the gravitational results found in [2].…”
Section: Introductionmentioning
confidence: 68%
“…With this result for boosted ensembles on the line in hand, we next analyse the case of rotating ensembles on the circle. Gravitational computations of the OTOC have found that in the Lyapunov regime the instantaneous Lyapunov exponent exhibits a sawtooth pattern which when averaged over a full period gives an averaged Lyapunov exponent controlled by the temperature [1,2]. We show that in the Lyapunov regime, where the global conformal block of the stress tensor dominates, the OTOC on the circle can be obtained by that on the line from a reasoning that involves the relation between global conformal blocks and geodesic Witten diagrams.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Indeed, tidal stresses have been found to be significant also in horizonless microstate geometries [10][11][12][13] that, seen from a distance, resemble black holes. These geometries are also associated with scrambling [14], another probe of strong gravity. Finally, evanescent modes are related to the strong gravity inside the innermost stable orbits, but the relation to mixing is less clear.…”
Section: Jhep08(2021)085mentioning
confidence: 96%